Safar voyage - Daftari, Fereshteh; Baird, Jill 1958-; Shelton, Anthony; Sohrabi, Naghmeh; Gregory, Derek 1951-; Salloum, Jayce (Douglas & McIntyre, 2014)
Safar/Voyage features a selection of recent artwork by artists from Iran, Turkey and a range of Arab countries. The text -- illustrated with more than fifty colour photographs, archival images and a map of the region -- explores themes of migration, dislocation, and changing identity and addresses the impact of war and revolution on individuals, communities and culture in this highly contested region of the world. Echoing the title, curator Fereshteh Daftari constructs a journey through the work of the eighteen artists featured in the book. Political geographer Derek Gregory questions the West's assumptions about the Middle East by asking "Middle of what? East of where?" Offering a counterpoint to Western travellers exoticizing the Middle East, historian Naghmeh Sohrabi examines the experiences of 19th century travellers from the Middle East to the West. Canadian Lebanese artist Jayce Salloum offers a visual essay that responds to the themes of voyage and dislocation. The artwork featured in Safar/Voyage includes photography, installation art, a carpet, a wall mural, painting, and sculpture
Keywords: Geschichte 2000-2011; Kunst; Arabische Staaten; Iran; Türkei; Art, Arab / 21st century / Exhibitions; Art, Iranian / 21st century / Exhibitions; Art, Turkish / 21st century / Exhibitions; Art, Arab; Art, Iranian; Art, Turkish; 2000-2099; Exhibition catalogs; Ausstellungskatalog -- Museum of Anthropology -- 20.04.2013-15.09.2013 -- Vancouver (British Columbia)